Severity of the clinical presentation of hepatitis A in five European countries from 1995 to 2014. (May 2022) - Severi, Ettore; Georgalis, Leonidas; Pijnacker, Roan; Veneti, Lamprini; Turiac, Iulia Adelina; Chiesa, Flaminia; Rizzo, Caterina; Martinelli, Domenico; Vold, Line; Herrador, Bernardo Guzman; Martinez, Carmen Varela; Sanchez, Elena Vanessa Martinez; et al.
Highlights: Symptoms and severity of hepatitis A increase with age and in vulnerable patients. Hepatitis A notification and hospitalisation rates are decreasing in Europe. In Europe, increasing age at hospitalisation is not reflected in increased severity. In Europe, older patients with liver diseases remain at increased risk of severe disease. Abstract: Objectives: We analysed hepatitis A (HepA) notifications and hospitalisations in Italy, the Netherlands, Norway, Spain, and Sweden for available periods between 1995 and 2014. We aimed to investigate whether decreasing HepA incidence is associated with increasing age at infection and worsening HepA presentation and to identify groups at risk of severe disease. Methods: We performed a retrospective cohort study including 36 734 notified and 36 849 hospitalised patients. We used negative binomial regressions to identify over time: i) trends in hospitalisation and notification rates; ii) proportion of hospitalised and notified patients aged ≥40 years; iii) proportion of "severe hospitalisations"; and iv) risk factors for severe hospitalisation. Results: During the study period both HepA notifications and hospitalisations decreased, with notification rates decreasing faster, patients aged ≥40 years increased, however, the proportion of severe HepA hospitalisations remained stable. Older patients and patients with comorbidities, particularly liver diseases, were more likely to experience severe disease. Conclusions: We used digitalised health information to confirm decreasing trends in HepA hospitalisations and notifications, and the increasing age of patients with HepA in Europe. We did not identify an increase in the severity of the clinical presentation of patients with HepA. Older patients with liver diseases are at increased risk of severe disease and should be prioritised for vaccination.